Pola pendidikan karakter di Pondok Pesantren Annuqayah Lubangsa Selatan Guluk-Guluk Sumenep - Zaitur Rahem; Ach. Zabidi (LP3M UNZAH GENGGONG, 2025)
Islamic boarding schools play a central role in shaping human resources with religious, moral, and social character. In the modern context, Islamic boarding schools face the enormous challenge of maintaining their educational authority and relevance without abandoning classical scholarly traditions. This research was conducted at the Annuqayah Lubangsa Selatan Islamic Boarding School, Guluk-Guluk, Sumenep, which is known for its significant contribution in fostering students through a structured management system. The purpose of this study is to analyze the patterns of administrators in building the educational authority of Islamic boarding schools, the strategies used in maintaining this authority amid the challenges of modernity, and its impact on student behavior. The research method used was qualitative with a field study approach. Data were obtained through observation, in-depth interviews, and documentation, then analyzed using an interactive analysis model that emphasized data reduction, presentation, and verification. The results of the study show that the educational authority of Islamic boarding schools is built through synergy between formal structures, moral exemplary behavior, and the internalization of religious values. The management's strategy in maintaining authority is carried out by strengthening Islamic boarding school traditions, using a persuasive-humanistic approach, institutional synergy, and utilizing internal media as a means of education. The impact of this authority is evident in the formation of students who are disciplined, religious, civilized, and able to live in a community with a high level of solidarity. Educational authority at the Annuqayah Lubangsa Selatan Islamic Boarding School is collective, adaptive, and based on Islamic values, thereby shaping students who are spiritually, morally, and socially mature.